Why do people persist in sea-level rise threatened coastal regions? Empirical evidence on risk aversion and place attachment - Ivo Steimanis (Elsevier, 2021)
Climate change is projected to increase the number of extreme weather events, which may lead to cascading impacts, feedbacks, and tipping points not only in the biophysical system but also in the social system. To better understand societal resilience in risky environments, we analyzed people’s attachment to place, their willingness to take risks, and how these change in response to extreme weather events. We conducted a survey with 624 respondents at the forefront of climate change in Asia: the river deltas in Bangladesh and Vietnam. Our findings confirm that most people prefer staying. Yet crucially, we find that (i) self-reported experiences of climate-related hazards are associated with increased risk aversion and place attachment, reinforcing people’s preferences to stay in hazardous environments; (ii) people with experiences of hazards are more likely aspiring to move to high-income destinations, arguably being beyond the reach of their capacities; and (iii) changes in aspirations to move abroad are connected to the changes in risk aversion and place attachment. The fact that preferences are associated with cumulative experiences of hazards and interact with aspirations to move to high-income destinations may contribute to our understanding of why so many people stay in hazardous environments.